심리적 임파워먼트가 정보보안 준수의도에 미치는 영향: 조직 신뢰와 조직 공정성의 조절 효과를 중심으로 - 황인호(Inho Hwang) (디지털콘텐츠학회논문지, 2021)
조직 내 정보 관리가 핵심 운영 조건으로 인식되면서, 조직들은 정보보안 정책 및 기술을 도입하여 조직 구성원의 보안 준수 행동을 요구하고 있다. 그러나, 조직은 구성원의 모든 보안 행동을 통제할 수 없으므로, 자발적인 보안 준수 행동을 위한 동기 형성에 관심을 가져야 한다. 본 연구는 조직 내부자의 정보보안 준수 의도 향상에 영향을 주는 내재적 동기인 심리적 임파워먼트의 중요성을 제시하고, 조직 차원에서 임파워먼트를 강화할 수 있는 방향(조직 신뢰 및 공정성)을 제시한다. 본 연구는 선행연구를 통해 연구 모델 및 가설을 제시하였으며, 구조방정식 모델링을 적용하였다. 연구 대상은 정보보안 정책을 적용하는 조직의 구성원으로 하였으며, 352개 표본을 가설 검증에 적용하였다. 분석 결과, 심리적 임파워먼트(영향력, 능력, 의미성)가 준수 의도에 긍정적 영향을 주었으며, 조직 신뢰와 조직 공정성이 심리적 임파워먼트와 준수 의도 간의 관계를 조절하였다. 본 연구는 조직 구성원의 정보보안 목표 수준 달성을 위해, 조직원에게 부여할 수 있는 내재적 동기와 조직 환경 요인을 복합적으로 제시하였다는 측면에서 시사점을 가진다. As information management is recognized as a core operational factor, organizations are demanding information security (IS) compliance behaviors of employees through adoption in IS policies and technologies. This study suggests the importance of psychological empowerment that affects the improvement of IS compliance intentions of insiders and suggests ways to strengthen the empowerment at the organizational level. We presented research hypotheses through previous studies, and verified the research hypotheses through structural equation modeling. And we selected the research subjects as members of organizations that apply IS policies, and applied 352 samples to hypothesis testing. As a result of the analysis, psychological empowerment (impact, competence, meaning) had a positive effect on IS compliance intention, and organization trust and organization justice moderated the relationship between psychological empowerment and IS compliance intention. This study has implications in terms of presenting the intrinsic motivation and organizational environmental factors that can be given to employees in order to achieve internal IS goals. KCI Citation Count: 5